Drug Transporter Expression and Activity in Human Hepatoma HuH-7 Cells - Elodie Jouan; Marc Le Vée; Claire Denizot; Yannick Parmentier; Olivier Fardel (MDPI AG, 2016)
Human hepatoma cells may represent a valuable alternative to the use of human hepatocytes for studying hepatic drug transporters, which is now a regulatory issue during drug development. In the present work, we have characterized hepatic drug transporter expression, activity and regulation in human hepatoma HuH-7 cells, in order to determine the potential relevance of these cells for drug transport assays. HuH-7 cells displayed notable multidrug resistance-associated protein (MRP) activity, presumed to reflect expression of various hepatic MRPs, including MRP2. By contrast, they failed to display functional activities of the uptake transporters sodium taurocholate co-transporting polypeptide (NTCP), organic anion-transporting polypeptides (OATPs) and organic cation transporter 1 (OCT1), and of the canalicular transporters P-glycoprotein and breast cancer resistance protein (BCRP). Concomitantly, mRNA expressions of various sinusoidal and canalicular hepatic drug transporters were not detected (NTCP, OATP1B1, organic anion transporter 2 (OAT2), OCT1 and bile salt export pump) or were found to be lower (OATP1B3, OATP2B1, multidrug and toxin extrusion protein 1, BCRP and MRP3) in hepatoma HuH-7 cells than those found in human hepatocytes, whereas other transporters such as OAT7, MRP4 and MRP5 were up-regulated. HuH-7 cells additionally exhibited farnesoid X receptor (FXR)- and nuclear factor erythroid 2-related factor 2 (Nrf2)-related up-regulation of some transporters. Such data indicate that HuH-7 cells, although expressing rather poorly some main hepatic drug transporters, may be useful for investigating interactions of drugs with MRPs, notably MRP2, and for studying FXR- or Nrf2-mediated gene regulation.